Militarisation Under COVID-19: Understanding the Differential Impact of Lockdown on the Forests of Colombia - Amador-Jiménez, Mónica; Millner, Naomi (Frontiers in Human Dynamics, 2021)
This paper examines the increase in deforestation in Colombia in 2020 that partially coincided with the ‘lockdown’ imposed to curb the spread of COVID-19. Early media analysis linked this with the redeployment of military forces away from forest protection to impose lockdown restrictions. However, closer investigation reveals significant regional variation in both the reorganisation of military groups and in the rate at which deforestation has materialised; military presence has increased in some regions, while in others deforestation has increased. To explain this, we unpack the ‘biopolitical’ dimensions of international conservation to show how the specific deployment of military groups in Colombia reflects an interplay between notions of the protection of (species) life, longer colonial histories, and more recent classification of geographies in terms of riskiness and value. Drawing on qualitative analysis and anthropological histories, we argue that deforestation rates in the Inter-Andean Valleys and in the Amazon Belt of Colombia reflect the specific role of the military in different articulations of the political forest along with new connections between conservation and the war on drugs.